1963
DOI: 10.1063/1.1734319
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Cl2 in Shock Waves

Abstract: The dissociation of Cl2 in Cl2–Ar mixtures was measured in a shock tube over the temperature range 1700° to 2500°K. Direct absorption spectrophotometry was used to follow the course of the reaction. A rate constant given by k=8.90×1013 exp —48 300/RT cm3/mole-sec [or,alternatively,k=3.13×1012(57 080/RT)2.087exp−57 080/RT cm3/mole·sec]was found to fit the measured data over the entire temperature range with a most probably error of ±6%. The activation energy determined agreed exactly with that measured by Hirao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Although r,(Cl,-Ar) has not been measured, and thus cannot be compared to z,(Cl,-Ar) presently calculated, the value obtained is not unreasonable; furthermore the method (28) predicts .c,(Cl,-He) in good agreement with experiment (30). The optical extinction coefficients for C1, at 3850 and 3640 A have been reported (31,32). For the purposes of computation, the (unknown) total pressures were chosen in such a way that no more than 5% of dissociation occurred in the first 5 ps of the reaction.…”
Section: (C) C12-ar Systemmentioning
confidence: 68%
“…Although r,(Cl,-Ar) has not been measured, and thus cannot be compared to z,(Cl,-Ar) presently calculated, the value obtained is not unreasonable; furthermore the method (28) predicts .c,(Cl,-He) in good agreement with experiment (30). The optical extinction coefficients for C1, at 3850 and 3640 A have been reported (31,32). For the purposes of computation, the (unknown) total pressures were chosen in such a way that no more than 5% of dissociation occurred in the first 5 ps of the reaction.…”
Section: (C) C12-ar Systemmentioning
confidence: 68%
“…[94], and Blauer et al [97]. The data from Jacobs and Giedt and from Blauer et al were obtained for the reverse reaction and converted through the equilibrium constant in the present work.…”
Section: Discussionmentioning
confidence: 86%
“…The high values have been attributed to boundary layer effects and limitations in detection accuracy and were disregarded by both Lloyd [91] and Baulch et al [30]. The data from Jacobs and Giedt [94], van Thiel et al [95], and Carabetta and Palmer [96] are in good agreement and these data form the basis for the recommendation of Lloyd [91]. The third group of data, reported by Blauer et al [97] and Santoro et al [98], indicate a rate constant for Cl + Cl + Ar that is about a factor of five below the bulk data.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…Both Jacobs and Giedt [23] and van Thiel et al [24] found impurities of up to 10% in their samples of chlorine supplied by the same manufacturer. The former noted air contamination, while the latter identified C 0 2 as the impurity.…”
Section: A Dissociationmentioning
confidence: 92%
“…The methods employed by Hiraoka and Hardwick [22], Jacobs and Giedt [23], and van Thiel, Seery, and Britton [24] are essentially the same: incident shock waves were used and the reaction monitored by absorption spectroscopy.…”
Section: A Dissociationmentioning
confidence: 99%